Analisis Sistem Akuntansi Penerimaan Kas Dalam Mendukung Pengendalian Intern UD. Gemilang Bangil - Khamdan Suriyok (Fakultas Ekonomi Universitas Panca Marga, 2022)
The Purpose of This Research Is To Know And Analyze The Implementation Of Cash Receipts Accounting System For Cash Sales That Are Applied To UD. Gemilang Bangil So That It Can Support Internal Control, The Informants In This Research Are The Production Department, Sales Section, Cash Section, Finance Section, Packaging Section And Shipping Section. The results of this study indicate that the cash receipts accounting system for cash sales at UD. Gemilang Bangil Overall It's Good Enough. However, there is still a need for improvement regarding the cash receipts accounting system for cash sales, which of course relates to the organizational structure, documents, and accounting records used as well as cash receipts procedures for cash sales at UD. Brilliant Bangil. Conclusion There is a need for improvements in the cash receipts section for cash sales, this is done so that monitoring can be easily carried out and prevent fraud that may occur if the problem is not resolved. To solve this problem, the author provides useful troubleshooting for the company. Keywords: Cash Receipts, and Internal Control